Inferring Suspended Sediment Carbon Content and Particle Size at High Frequency From the Optical Response of a Submerged Spectrometer. Issue 5 (9th May 2022) - Sehgal, Dhruv; Martínez‐Carreras, Núria; Hissler, Christophe; Bense, Victor F.; Hoitink, A. J. F. (Ton)
Abstract: Real time monitoring of suspended sediment (SS) carbon content and particle size information is essential to understand SS transport mechanisms and processes. However, limited in situ methods are available, and manual and unattended sampling makes high frequency observation challenging. Based on evidence that optical measurements of SS concentration are dependent on particle size and composition, we hypothesize that SS carbon content and mean particle size D ‾ $\left(\overline{D}\right)$ can simultaneously be inferred from the absorbance data measured with a submerged spectrometer at high frequency. With the aim to predict both parameters, we investigate if global calibrations can be obtained and used instead of site‐dependent local calibrations. To test this, we created a laboratory data set using a tank setup, and an in situ field data set. Sediment samples varying in composition were collected and used in a tank setup to obtain global (all sites grouped together) calibrations between absorbance, particle size and carbon content. Two sites were instrumented to collect in situ field data, to generate local (site‐specific) calibrations and to validate the global calibrations obtained in the laboratory. A procedure to account for the effect of SS concentration when using the global calibration to predict D ‾ $\overline{D}$ is also presented. Our findings indicate that global calibrations can accurately predict D ‾ $\overline{D}$ from in situ absorbance readings, with a median absolute error of 17.3 μm, versus 10.5 μm for a local calibration. Local calibrations are indispensable to reliably predict carbon content, with a median absolute error of 1.3%. Plain Language Summary: Transport of suspended sediments (SSs) within a river is a temporally dynamic process that can best be monitored with in situ sensors. Turbidity meters are optical sensors that measure the amount of light scattered by the SS in water and are normally used to estimate SS concentrations. However, they are known to be sensitive to SS properties, such as carbon content and particle size, requiring local calibrations at each new measurement site. This study uses a submerged spectrometer, an optical sensor, measuring absorbance in the UV‐Visible range to quantify SS carbon content and mean particle size in situ and at high frequency, in a quest to obtain global instead of site‐specific local calibrations. To test the proposed method, we performed laboratory experiments with sediment samples from six sites and used the in situ data measured at two instrumented sites. We conclude that a global calibration is obtained to predict mean particle size from absorbance, whereas local calibrations are still needed to predict SS carbon content. This knowledge on SS carbon content, a major organic SS component, and particle size is needed to improve SS transport modeling and eventually better understand SS transport mechanisms. Key Points: We predict suspended sediment (SS) mean particle size and carbon content from the absorbance measured by a submerged spectrometer A global calibration for predicting mean particle size allows the use of a near‐constant calibration instead of local calibrations In situ high frequency information on SS properties enable measurement of non‐stationary events at a small time scale